Volume-dependent effect of perihaematomal oedema on outcome for spontaneous intracerebral haemorrhages. Issue 5 (23rd January 2013) - Appelboom, Geoffrey; Bruce, Samuel S; Hickman, Zachary L; Zacharia, Brad E; Carpenter, Amanda M; Vaughan, Kerry A; Duren, Andrew; Hwang, Richard Yeup; Piazza, Matthew; Lee, Kiwon; Claassen, Jan; Mayer, Stephan; et al.
Abstract : Introduction: It is still unknown whether subsequent perihaematomal oedema (PHE) formation further increases the odds of an unfavourable outcome. Methods: Demographic, clinical, radiographic and outcome data were prospectively collected in a single large academic centre. A multiple logistic regression model was then developed to determine the effect of admission oedema volume on outcome. Results: 133 patients were analysed in this study. While there was no significant association between relative PHE volume and discharge outcome (p=0.713), a strong relationship was observed between absolute PHE volume and discharge outcome (p=0.009). In a multivariate model incorporating known predictors of outcome, as well as other factors found to be significant in our univariate analysis, absolute PHE volume remained a significant predictor of poor outcome only in patients with intracerebral haemorrhage (ICH) volumes ≤30 cm 3 (OR 1.123, 95% CI 1.021 to 1.273, p=0.034). An increase in absolute PHE volume of 10 cm 3 in these patients was found to increase the odds of poor outcome on discharge by a factor of 3.19. Conclusions: Our findings suggest that the effect of absolute PHE volume on functional outcome following ICH is dependent on haematoma size, with only patients with smaller haemorrhages exhibiting poorer outcome with worse PHE. Further studies are needed to define the precise role of PHE in driving outcome following ICH.